Autogenous bonding of tooth fragment retained in lower lip after trauma - Andrea Lips; Luciana Pereira da Silva; Patricia Nivoloni Tannure; João Alfredo Farinhas; Laura Guimarães Primo; Gloria Fernanda Barbosa de Araújo Castro (Wolters Kluwer Medknow Publications, 2012)
In cases of trauma, dental fragments occasionally penetrate into the soft-tissues and may cause severe complications, if neglected. Clinical and radiographic examinations can provide a diagnosis and help in the surgical removal of any dental fragment embedded in soft-tissue. This case report concerns an 8-year-old boy who was diagnosed with a fragment of a fractured permanent central incisor crown located in the lower lip. The patient was seen initially at a general hospital, where the dental fragment went unnoticed. After 2 days, the patient was seen at the pediatric dentistry clinic, where a fragment embedded in the lower lip, causing a large swelling, was diagnosed. The fragment was removed surgically and bonded to the fractured tooth. A mouth guard was prescribed for sports. The importance of soft-tissue exploration even post-trauma was highlighted in this paper.